Citizens' perceptions of the presence and health risks of synthetic chemicals in food: results of an online survey in Spain - José Pumarega; Cristina Larrea; Araceli Muñoz; Natàlia Pallarès; Magda Gasull; Giselle Rodríguez; Manel Jariod; Miquel Porta (Elsevier, 2017)
Objective: To explore factors influencing perceptions and viewpoints on the responsibility for the presence of toxic substances in food, on enforcement of laws and regulations that control human exposure to toxic substances in food, and on the effectiveness of such regulations. Methods: An online survey was completed by 740 individuals from several parts of Spain (median age, 47 years; 67% were women; 70% had completed university studies). Results: Over 87% of respondents said that it was possible that throughout their lives they could have accumulated in their body toxic substances potentially dangerous to their health. The attribution of the responsibility for toxic substances in food to a larger number of social groups was more frequent among respondents who consulted information about the problem more often (odds ratio [OR]: 1.92), who correctly identified factors that increase the likelihood of toxic substances in food being harmful to human health (OR: 2.86), who better knew the health problems that may be caused by such substances (OR: 2.48), and who recognised more food groups that tend to have concentrations of toxic substances potentially harmful to health (OR: 2.92) (all p values <0.001). Women were 65% less likely than men to answer that regulations on toxic substances in food are effective (p < 0.001); and so were participants who identified more food groups with potentially toxic concentrations. Conclusions: Among study participants there was a widespread scepticism and distrust towards the enforcement and effectiveness of laws and regulations that in Spain aim to control human exposure to toxic substances in food.